Comparative Assessment of Antibiotic Resistance in Lactic Acid Bacteria Isolated from Healthy Human Adult and Infant Feces - Pawar, Rasika; Zambare, Vasudeo; Nabar, Bela (Nepal Journal of Biotechnology, 2020)
Lactic acid bacteria are normal inhabitants of the gastrointestinal tract of humans. Their occurrence in infant and adult feces is abundant. The current study assesses and compares the antibiotic resistance in lactic acid bacteria isolated from healthy human adult and healthy infant fecal samples. A total of 255 lactic acid bacteria isolates (126 from adult feces and 129 from infant feces) were isolated and characterized from 60 fecal samples. Lactobacillus spp., Pediococcus spp. and Enterococcus spp. were included in the study. The study was done using the WHONET software for the analysis of antibiotic susceptibility data of lactic acid bacteria. Most of the Lactobacillus and Pediococcus strains were sensitive to vancomycin. Enterococcus strains showed resistance against vancomycin. Ampicillin, ciprofloxacin and cefuroxime resistance were significantly (p<0.05) higher in Lactobacillus strains isolated from adult fecal samples than those isolated from infant fecal samples. A similar pattern was observed in Enterococcus strains with erythromycin, gentamycin and tobramycin resistance. Pediococcal isolates from adult feces showed significantly higher resistance against tobramycin, ciprofloxacin, gentamycin, cefotaxime and cefuroxime in comparison with infant fecal isolates. Antibiotic resistance was exhibited by lactic acid bacteria against most commonly used antibiotics and it was higher in strains isolated from adult fecal samples than in the strains isolated from infant fecal samples. The increasing trend in antibiotic resistance from infant to adult might be due to food habits and antibiotic intakes. Thus, the widespread antibiotic resistance in different lactic acid bacteriamay pose a food safety concern as well.